New species and records of Ischnosoma Stephens (Coleoptera: Staphylinidae: Tachyporinae) from Nepal - Kocian, Matúš; Schülke, Michael (Zootaxa, 2018)
More than 540 specimens of the genus Ischnosoma Stephens (Coleptera, Staphylinidae, Tachyporinae) from Nepal are revised. Four new species are described and illustrated: Ischnosoma bhojpur Kocian & Schülke, sp. n., I. hirthei Kocian & Schülke, sp. n., I. jumla Kocian & Schülke, sp. n. and I. schmidti Kocian & Schülke, sp. n. Additional records of previously described species are reported. The distributions of the Nepalese species are mapped. Ischnosoma gratiosum (Cameron, 1932) is recorded from Nepal for the first time. A revised key to the Ischnosoma species of Nepal is presented.